Potential of Instant Temulawak (Curcuma xanthorrhiza Roxb.) as an Immunomodulatory Agent against Viral Infections: A Systematic Narrative Review - Firmansah, Moh.; Thaher, M Iman Tarmizi; Palungan, Juliana; Dewa, Sima Asmara; Rahmah, Winda Wahyu Setya; Arta, Alfa Frista; Fauziyah, Ageng Hasna (Indonesian Journal of Science and Pharmacy, 2026)
The COVID-19 pandemic has significantly increased public interest in traditional herbal medicines, particularly instant temulawak (Curcuma xanthorrhiza Roxb.), as immune-boosting agents. This systematic narrative review evaluates the immunomodulatory and antiviral potential of temulawak's bioactive compounds, especially curcuminoids, in the context of instant herbal formulations. A comprehensive literature search was conducted across PubMed, Google Scholar, Scopus, and Science Direct using Boolean operators. From 247 initial records, 38 articles met the inclusion criteria. Evidence demonstrates that curcuminoids exhibit broad-spectrum antiviral activity against SARS-CoV-2, influenza, hepatitis B/C, dengue, and HIV through inhibition of viral entry, replication, and modulation of NF-κB, MAPK, and JAK/STAT signaling pathways. Immunomodulatory effects include enhanced macrophage function, T-cell modulation, and cytokine balance regulation. A notable case report showed C. xanthorrhiza consumption led to HBsAg seroconversion in a chronic hepatitis B patient. However, critical gaps persist regarding the specific efficacy of instant formulations, bioavailability challenges of curcumin in processed forms and the absence of rigorous clinical trials on temulawak instan specifically. Future research should prioritize standardized formulations, bioavailability optimization, and clinical validation to bridge the translational gap between in vitro evidence and practical herbal applications.